Performance Analysis of an Unreliable Queuing System with Buffer - Rindzevičius, R.; Tervydis, P. (Elektronika ir Elektrotechnika, 2009)
We propose analysis of a data network node, which uses main and reserve transmission channels. Analytical analysis of a queuing system M/M/2(N)K with unreliable main transmission channel and buffer threshold control is based on the Markov chains. The system has operation mode which is controlled by means of buffer threshold control strategy. Exact analysis of queues for finite system buffer with threshold control is implemented. The data packets loss probabilities and other main performance measures of queuing system are derived. Numerical results are presented to demonstrate the feasibility of the presented data packets transmission algorithms. Optimization problem is considered and numerical examples are presented. By tuning the buffer threshold, a compromise can be achieved between quality of data packet transmission and used channels throughput. Using proposed simulation of G/G/2/(N)K queuing system model and analytical M/M/2/(N)K system model it is possible to evaluate the system’s performance measures. Ill. 12, bibl. 6 (in English; summaries in English, Russian and Lithuanian).